(untitled) (Italian Journal of Public Health, 2010)
Background: Since its discovery, AIDS has been a major pandemic infection. Nowadays, despite high levels of awareness, HIV infection is still one of the most complex phenomenon in our society and people, especially young people, don’t apply changes to reduce sexual risk behaviour to bring about prevention of HIV and AIDS. Condom use, particularly consistent use, is suboptimal in our communities. In our country, for Family Planning Worldwide 2008, just 38,3% of young people reported to use condoms. Monogamy and harmonious relationships play a positive role in young people and reduce their risk of HIV infection and such aspects of relationship contexts could form a significant part of the progressive strategies required for HIV-prevention interventions to be successful. Many prevention campaigns have been realized and in particular they try to explain the risk connected to HIV and give information about how to prevent infection and the infection’s course. The next generation of HIV prevention and risk reduction interventions should move beyond basic sex education and condom use / availability. Successful interventions must optimize strategies that support HIV risk reduction behaviours. Despite extensive behavioural research, current strategies have not resulted. Methods: In this article we explain why the old campaign didn’t work and why youth initiatives could be a possible answer to a prevention needs. We choose the method of peer education and scientific contents using transverse knowledge from expert of medicine, psychology and media science to face off at the needs of efficacy and reliability. Results: The final sample is made by 271 students, 102 males, 164 females. 91,5% declare that had already sexual relations, instead 5,19% never had one. 38,% of sample affirm to use habitually condoms, 20,3% sometimes, 18,8% never used condoms. Conclusions: This study shows how new approach to the problem could help people changing their behaviors